Soundscapes als akustisches Gedächtnis der Stadt: künstlerische Strategien gegen Gentrifizierung. - Brunow, Dagmar (Ventil-Verl., 2011)
In the view of soundscape research, noisy events are part of the total acoustical environment which also includes evaluation and variation of non-acoustical environmental factors as well as subjective factors regarding the persons concerned [1]. As there are little empirical data available on subjective attitudes and evaluations of such an acoustical environment in our society, 922 persons were interviewed by questionnaire with regard to comfortable and uncomfortable sounds, typical sounds of our times, and their attitude towards quietness resp. silence. The results allow for the conclusion that individual attitudes and experiences regarding antipoles to noise provide important links for a positive reshaping of our acoustical environment.
Quietness, silence, pleasant sounds - a survey on potential noise antagonists.
Keywords: Stadtsoziologie; Mieter; Bewohner; Kunst; Experiment; Stadtlandschaft; Gentrifizierung; Verdrängung; Aufwertung; Intervention; Stadtrundgang; Geräusch; Klang; Kunstprojekt; Hören